Aspects of signal processing with emphasis on underwater acoustics / edited by G. Tacconi - 429179 NATO Advanced Study on Signal Processing with Emphasis on UNderwater Acoustics (1976 : Portovenere, La Spezia); Tacconi, G. (Dordrecht, Holland D. Reidel, 1977)
13